L'imaginaire du démoniaque dans la Septante Une analyse comparée de la notion de "demon" dans la Septante et dans la Bible Hébraïque - Angelini, Anna (BRILL, 2021)
This book offers a thorough analysis of demons in the Hebrew Bible and Septuagint in the wider context of the ancient Near East and the Greek world. Taking a fresh and innovative angle of enquiry, Anna Angelini investigates continuities and changes in the representation of divine powers in Hellenistic Judaism, thereby revealing the role of the Greek translation of the Bible in shaping ancient demonology, angelology, and pneumatology. Combining philological and semantic analyses with a historical approach and anthropological insights, the author both develops a new method for analyzing religious categories within biblical traditions and sheds new light on the importance of the Septuagint for the history of ancient Judaism. Le livre propose une analyse approfondie des démons dans la Bible Hébraïque et la Septante, à la lumière du Proche Orient Ancient et du contexte grec. Par un nouvel angle d'approche, Anna Angelini met en lumière dynamiques de continuité et de changement dans les représentations des puissances divines à l'époque hellénistique, en soulignant l'importance de la traduction grecque de la Bible pour la compréhension de la démonologie, de l'angélologie et de la pneumatologie antiques. En intégrant l'analyse philologique et sémantique avec une approche historique et des méthodes anthropologiques, l'autrice développe une nouvelle méthodologie pour analyser des catégories religieuses à l'intérieur des traditions bibliques et affirme la valeur de la Septante pour l'histoire du judaïsme antique
Keywords: Bibel -- Altes Testament; Bibel -- Altes Testament -- Septuaginta; Jewish demonology; Monsters in the Bible; Monsters; Meerwesen; Ungeheuer